Secondary Use and Analysis of Big Data Collected for Patient Care - Martin-Sanchez, F. J.; Aguiar-Pulido, V.; Lopez-Campos, G. H.; Peek, N.; Sacchi, L. (Yearbook of Medical Informatics, 2017)
Objectives: To identify common methodological challenges and review relevant initiatives related to the re-use of patient data collected in routine clinical care, as well as to analyze the economic benefits derived from the secondary use of this data. Through the use of several examples, this article aims to provide a glimpse into the different areas of application, namely clinical research, genomic research, study of environmental factors, and population and health services research. This paper describes some of the informatics methods and Big Data resources developed in this context, such as electronic phenotyping, clinical research networks, biorepositories, screening data banks, and wide association studies. Lastly, some of the potential limitations of these approaches are discussed, focusing on confounding factors and data quality.Methods: A series of literature searches in main bibliographic databases have been conducted in order to assess the extent to which existing patient data has been repurposed for research. This contribution from the IMIA working group on “Data mining and Big Data analytics” focuses on the literature published during the last two years, covering the timeframe since the working group’s last survey.Results and Conclusions: Although most of the examples of secondary use of patient data lie in the arena of clinical and health services research, we have started to witness other important applications, particularly in the area of genomic research and the study of health effects of environmental factors. Further research is needed to characterize the economic impact of secondary use across the broad spectrum of translational research.
Keywords: Electronic health record; medical informatics; data mining; clinical study; translational medical research